Control and prevention of tuberculosis in Britain: an updated code of practice. Subcommittee of the Joint Tuberculosis Committee of the British Thoracic Society. (1990)
A subcommitte was appointed by the Joint Tuberculosis Committee of the British Thoracic Society to review and bring up to date guidelines on control measures for tuberculosis. The updated code of practice emphasises that all cases of tuberculosis must be notified. A minority of patients need admission, and those with positive sputum smears should be regarded as infectious until they have received two weeks of chemotherapy. NHS staff at risk should be protected, and evidence of infectious tuberculosis should be sought as routine among certain prospective NHS employees, schoolteachers, and others. Contact tracing should be vigorously pursued, and all entrants to Britain from countries where tuberculosis is common should be screened. BCG vaccination should be offered in selected instances, and local organisation of tuberculosis services should be extended.